Trade-off analyses and optimization of water-related ecosystem services (WRESs) based on land use change in a typical agricultural watershed, southern China. (10th January 2021) - Liang, Jie; Li, Shuai; Li, Xiaodong; Li, Xin; Liu, Qiang; Meng, Qianfang; Lin, Anqi; Li, Jinjin
Abstract: As the direct manifestation of human activities, land use change is the main driving factor in variations in ecological processes and ecosystem services (ESs). For better land use management in the future, it is essential to evaluate the changes of ESs affected by land use change and identify the relationships among ESs. In this study, four primary water-related ecosystem services (WRESs), including water yield, food production, water purification and soil conservation, were selected to assess the effects of past land use change (1980–2015) on WRESs in the Xiangjiang River Basin, a typical agricultural watershed in southern China. From 1980 to 2015, water yield, food production increased by 1.58% and 44.78%, respectively. And soil conservation was improved with a 13.11% decrease in sediment export. Because of the rapid expansion of agriculture and urbanization from 2000 to 2015, water purification was degraded significantly with the increase in nitrogen export (+22.56%) and phosphorus export (+25.85%). Trade-offs mainly occurred between water purification and other WRESs. Based on the existing ecological problem, four alternative land use scenarios were designed to explore the underlying effects of various land use polices. Among four scenarios, the combined scenario was selected as the optimal scenario because of the greatest improvement in water purification and small negative effect on food production. Our research provides an integrated WRESs trade-offs assessment framework. Moreover, the establishment of multiple land use scenarios based on land suitability evaluation could inform future land use decision-making and water conservation management in the agricultural watershed. Graphical abstract: Image 1 Highlights: We illustrate the changes of water-related ecosystem services (WRESs) based on past land use change using Invest model. Trade-offs mainly occurred between water purification and other WRESs. Scenario analysis method is applied to explore the underlying effects of different land use polices. The combined scenario is optimal for future land use pattern based on trade-off analyses.